Oral Submucous Fibrosis Association with Sociodemographic and Personal Habits of Dental Patients Visiting Tertiary Care Hospital in Hyderabad - Hassan Shahid; Abubakar Abdullah; Naveed Irfan; Sadia Hassan; Zafar Abbas; Syed Muhammad Ahmed Bukhari (Proceedings)
Introduction: Sociodemographic and personal habits are variable among patients with oral submucous fibrosis and are important to know to see the pattern of these factors in oral submucous fibrosis in local population.